Стан вікової звичайнодубової діброви (Querceta roboris) парку “Феофанія”, м. Київ (на прикладі 3, 5 та 6-го кварталів) - Klimenko, Yu.O.; Moroz, V.V.; Drujina, M.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2014)
Results of overall enumeration of plants in the biggest areas occupied by Querceta roboris in quarters 3, 5 and 6 of park Feofania (Kyiv city) are presented. It has been discovered that the biggest amount of oaks are in-between 52 and 72 cm in diameter, next in number are plants with stern diameter over 76 cm, plants with stern diameter of 48 cm or less are few. It is shown that the amount of age-old Querceta roboris totals from 21 to 69 units per 1 hectare (in 180 years-old plantations of the second creditworthiness with the first fullness it is supposed to amount to 140). The second floor is presented with Carpinus betulus, Tilia cordata, Acer platanoides and other species, population of which have a pronounced left-sided age specter. That indicates de gradation of Querceta roboris and the fact that without human intervention it will not recover itself. Age-old oak wood recovering measures has been presented; those measures constitute creating 0,08 hectare big and even bigger “windows” in the second floor and planting into those “windows” seedlings of Quercus robur.